Adventure time. Princess Bubblegum - Ward, Pendleton, 1982- (KaBoom!, a division of Boom Entertainment, Inc., 2020)
"Return to the Land of Ooo with this all-new collection of the most beloved stories about everyone's favorite tough gum from Adventure Time -- the incomparable Princess Bubblegum! From traveling into space to dealing with pesky poltergeists, there's nothing Bubblegum won't do to save the day -- even if Finn and Jake sometimes have to save her from her own good intentions! But no matter what happens, you can count on Princess Bubblegum to come through for her friends, because that's a royal promise -- and you can't break royal promises! Never, ever, never, no matter what, forever!"--Provided by publisher.